A CONTEXTUALIZAÇÃO DO PROGRAMA MAIS EDUCAÇÃO EM ESCOLAS DO MUNICÍPIO DE PONTA GROSSA/PR: DESAFIOS E PERSPECTIVAS DA GESTÃO ESCOLAR - MARTINS, ELISÂNGELA CHLEBOVSKI (2016)
This study analyzes the More Education Program (SMEs) in the context of the practice from the perspective of school management. The research is contextualized inside the broader political, intended to check how the context of the practice of factors are being influenced and articulated with the other contexts of public policy. In this way specifically we analyze the contexts that have influenced the development of SMEs and the guiding principles of this policy, investigating aspects related to the implementation of the program and how the subjects actualize the proposal in full-time municipal schools of Ponta Grossa / PR. We base the research on the approach of the policy cycle based on in Ball studies (2006 and 2011) and Mainardes (2006 and 2011), studies of Paro (2010), Souza (2012), Libâneo et al (2012) and Werle (2009) establish educational policies, educational management and school; studies on conceptions of full-time education were guided by Teixeira contributions (1959, 1994), Ribeiro (1986), Cavaliere (2007), Rabbit (2009), Guara (2006) and aspects relating to full-time schools were based from Moll studies (2012), Branco (2009), Mauritius (2009) and Menezes (2012). The research involved a study of SMEs, introducing the official reference that they support, in order to present its source, purpose, principles, goals and operations, aiming at a comprehensive analysis of the program. Finally we researched the implementation of SMEs in the city of Ponta Grossa / PR, where we conducted semistructured interviews with the Municipal Coordinator of SMEs and the Directors and Pedagogic Coordinators from two municipal schools that offer full-time education. The research results in practice in the context pointed out that SMEs merges with education policy implemented in full time in full-time schools in the city. The SME is an execution opportunity of a policy, planned by the local government, which sometimes takes an assistance character, but predominates as a financial and educational support for the offer of full-time education in view of the integral formation of students. The main challenge appointed by the school management in the implementation of the Programme was the discontinuance of financial transfers, however, in the context of the municipality, the schools that serve full time consider the consolidated polic.